Advantages and Disadvantages of Electronic Mortgage Registration Based on the Perspective of Business Administration Law - Surya Perdana; Triono Eddy; Rahmat Ramadhani (International Journal Reglement & Society (IJRS), 2022)
The process of registering mortgage rights electronically (HT-el) based on Permen HT-el Number 5 of 2020 is essentially a tangible manifestation of the applicability of the Business Administration Law which later transformed into a set of rules that regulate the legal relationship between business actors, namely between the giver and recipient of the mortgage and PPAT includes the rights and obligations of each with all the possibilities that occur after the registration of mortgage rights to the land office/BPN. In practice, HT-el registration has advantages and disadvantages based on the perspective of Business Administration Law. The type of research used in this paper is normative legal research with secondary data as the data source. Based on the outcomes of the study, it is known that the mechanism for registering HT-el based on Permen HT-el Number 5 of 2020 is to use an electronic system that separates the PPAT's duties in making the Mortgage Deed (APHT) with the PPAT's obligation to register mortgages that are integrated with the electronic system. to the land office/BPN. The implementation of HT-el registration as regulated in Permen HT-el Number 5 of 2020 based on the perspective of Business Administration Law has advantages and disadvantages